1991
DOI: 10.3382/ps.0701571
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pelleting, Salt, and Pentosanase on the Viscosity of Intestinal Contents and the Performance of Broilers Fed Rye

Abstract: An experiment was conducted to determine the impact of pelleting of rye, dietary salt (.39 and .57%), and crude pentosanase supplementation (0 and .2%) on the viscosity of intestinal contents and the concomitant performance of broiler chicks fed rye-based diets. Each treatment was replicated six times with six birds per replicate. Test diets were fed from 1 day to 3 wk of age, at which time body weight, feed intake, intestinal viscosity, and molecular weight distribution of carbohydrate complexes were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
2
8

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(80 citation statements)
references
References 13 publications
4
66
2
8
Order By: Relevance
“…Published values for viscosity of duodenal digesta from cattle are not available. However, the values observed are lower than those reported for total intestinal contents from broilers (Bedford et al 1991). Bedford (1996) indicated that increases of intestinal viscosity from 1 to 5 cP depressed diffusion of protein molecules of molecular weight of 1000 Da by as much as 40%.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Published values for viscosity of duodenal digesta from cattle are not available. However, the values observed are lower than those reported for total intestinal contents from broilers (Bedford et al 1991). Bedford (1996) indicated that increases of intestinal viscosity from 1 to 5 cP depressed diffusion of protein molecules of molecular weight of 1000 Da by as much as 40%.…”
Section: Discussioncontrasting
confidence: 48%
“…However, the values observed are lower than those reported for total intestinal contents from broilers (Bedford et al 1991). Bedford (1996) indicated that increases of intestinal viscosity from 1 to 5 cP depressed diffusion of protein molecules of molecular weight of 1000 Da by as much as 40%. Many intestinal luminal peptides are of molecular weight larger than the one indicated by Bedford (1996), such as the monitor peptide (61 amino acid residues) and the CCK releasing factor (1000-5000 Da) are involved in release of hormones such as CCK (Liddle 1995).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Part of the plant nutrients, such as starch and protein, are trapped within the insoluble cell walls (this is sometimes referred as cage effect) such that poultry are unable to access these nutrients (Englyst, 1989). Also, soluble fibers dissolve in the gut, forming viscous gels that trap nutrients and slow down rates of digestion and feed rate passage through the gut (Bedford et al, 1991;Veldman et al, 1994). …”
Section: Resultsmentioning
confidence: 99%
“…3.5-7.5 7.6-1 1 .5 1 1 .6-1 5.5 1 5. 6-19.5 19.6-23.5 Viscosity Range (cps) (Fengler and Marquardt 1988a, b), and incorporation of crude (Petterson and Aman 1989) or purified pentosanase (Grootwassink et al 1989) alleviates the effect by reducing the viscosity of intestinal contents (Bedford et al 1991 ;Teitge et al l99l). The solubilized pentosans, and the viscosity they confer, interfere with nutrient digestion and absorption.…”
Section: Trial2mentioning
confidence: 99%